2016
DOI: 10.1055/s-0036-1587335
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoperitoneum in the Setting of Pneumatosis Intestinalis in Children: Is Surgery Always Indicated?

Abstract: Pneumatosis intestinalis (PI) is a condition in which multiple gas-filled cysts form within the wall of the gastrointestinal tract in either the subserosa or submucosa. The presence of pneumoperitoneum in the presence of PI can present a therapeutic dilemma. The aim of our study was to review our experience and management of this condition. A single-center retrospective study of consecutive children (> 1 year) presenting with a pneumoperitoneum and evidence of PI (2009-2015). Demographics, case notes, microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In the setting of pneumatosis, the extent of mesenteric ischemia has been associated with poor outcomes including surgery and death in addition to pneumoperitoneum and/or portal venous gas (3,5,10,21,25,26); however, both pediatric and adult cases of pneumoperitoneum have been managed conservatively when patients are clinically stable suggesting some finding may represent ruptured cystic structures rather than transmural bowel wall perforation (12,(27)(28)(29)(30). In this study, conservative management was pursued in >50% of cases in the setting of pneumoperitoneum (11/ 16 episodes) and portal venous gas (3/6 episodes).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of pneumatosis, the extent of mesenteric ischemia has been associated with poor outcomes including surgery and death in addition to pneumoperitoneum and/or portal venous gas (3,5,10,21,25,26); however, both pediatric and adult cases of pneumoperitoneum have been managed conservatively when patients are clinically stable suggesting some finding may represent ruptured cystic structures rather than transmural bowel wall perforation (12,(27)(28)(29)(30). In this study, conservative management was pursued in >50% of cases in the setting of pneumoperitoneum (11/ 16 episodes) and portal venous gas (3/6 episodes).…”
Section: Discussionmentioning
confidence: 99%
“…Galea et al . suggested that the use of computed tomography (CT) scan is a very useful tool for evaluation of these patients as PI has been reported to be missed on plain abdominal X‐rays in 23% of patients in one study . However, Correlation could not be established between CT scan findings and severity of bowel ischaemia, which makes its value questionable except if other abdominal pathologies are suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Galea et al . recently published a group of seven patients, four of whom had global developmental delay and were similarly tube fed who had a presentation with pneumoperitoneum and were successfully managed conservatively …”
Section: Discussionmentioning
confidence: 99%
“…Intestinal pneumatosis and portal venous gas are important findings suggestive of intestinal disorders . The location of intestinal pneumatosis contributes to prognoses in these cases .…”
mentioning
confidence: 99%
“…I ntestinal pneumatosis and portal venous gas are important findings suggestive of intestinal disorders. [1][2][3][4][5][6][7][8][9][10][11] The location of intestinal pneumatosis contributes to prognoses in these cases. 1,3,5,6,9,[12][13][14][15][16] Previous reports have evaluated the location of pneumatosis using abdominal computed tomography (CT).…”
mentioning
confidence: 99%